MODEL PREVENTION OF COVID-19 IN PREGNANT MOTHERS AND FAMILY BASED ON LOCAL WISDOM : IN SONOAGENG VILLAGE BANYURIP HAMLET, PRAMBON DISTRICT NGANJUK DISTRICT - Nove Lestari; Nofi Juwitasari (STIKES dan AKZI Karya Husada Kediri, 2022)
Local wisdom is a person's attitudes and actions in response to changes in the physical and cultural environment, so that these attitudes and actions become new habits that must be carried out. The Local Wisdom-based Covid-19 prevention model is the use of local wisdom as an effort to prevent Covid-19 and as self-protection. Pregnant women are the main targets in preventing Covid-19 because changes in immunity that occur during pregnancy can make pregnant women more vulnerable to health problems, one of which is exposure to the Coronavirus. The purpose of this study was to determine the Covid 19 Prevention Model in Pregnant Women and Families Based on Local Wisdom in Sonoageng Village, Banyurip Hamlet, Prambon District, Nganjuk Regency. The research design is descriptive, with the research variable being the Covid-19 prevention model based on Local Wisdom. The population and sample are 30 respondents using the